PENGARUH PRESTASI DOSEN TERHADAP KELUARAN BERKUALITAS PADA STMIK ICHSAN GORONTALO - -, Rahmisyari (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
This study aimed to determine the effect of achievement faculty consisting of Frequency of Attendance, Level Pendidkan, Teaching Experience, and incentives for quality output either simultaneously or partially. This study is a population study, in which the data subject is tested through two stages of validity and reliability testing with a form of analysis that path analysis. The results of this study indicate that partial frequency of attendance (X1) effect on quality output at 71.9%, the level of education (X2) effect on quality output at 74.7%, teaching experience (X3) influence the quality output 75.3 % and incentives (X4) affect the quality output of 62.9%. simultaneous frequency of attendance (X1) education level (X2) teaching experience (X3) and incentives (X4) positive and significant impact on the quality output by 70.8% while the remaining 29.2% is influenced by variables that do not exist in the model. Keywords: Achievement Lecturer and Quality output